The media and food patterns in childhood (Research, Society and Development, 2022)
It is evident that food is directly related to the social and cultural context in which we live, which make these factors guide food patterns, from the price of food, such as religious issues and even the influence of advertising and the media, which have great power. to grab people's attention, especially children. In this way, the general objective of the research was to analyze the relationship of the media with childhood eating patterns and their influence on children's health. This is a bibliographic review research using the State of the Question, with the search for bibliographic material in the SCIELO, BDTD and Capes Periodicals Portal. The study shows that the foods published in the media are well accepted because they are attractive and tasty, but they are mostly ultra-processed and stimulate inadequate and insufficient food practices, which are risk factors for nutritional deficiencies, while excessive dietary patterns can generate overweight, obesity and other diseases, such as CNCDs. It is concluded that strategies must be taken to help reduce attitudes harmful to health as a way of guaranteeing the right to a balanced diet, controlling the marketing of food intended for children, such as the regulation of food advertising and the adoption of nutritional education actions in schools, protecting children, with the aim of preventing health problems in the short and long term.